Navarra y China. Punto de partida - Sánchez Fernández, Carlos (Huarte de San Juan. Geografía e Historia, 2006)
It is true and we are not wrong if we say that China is different. That difference does that we have to insist again and again that China is, if not the most difficult place to do business, it is one of the most difficult. But, after all the problems that we could find in any other country, is that DIFERENCE the one that is going to give us big headaches. That called cultural shock, different mentality or particular idiosyncrasy of the Asian people. But China is the country of the moment. It has a growth never saw in another country and a politics designed by the leaders to way – length term that seems to give its results. Who was going to think 25 year ago that China, in this period of time, was going to multiply its GDP by 7 to a growth per year of 8% or 10%? Who could foresee that today it would have a market economy instead of a planned economy? And now they have ahead another challenge as the differences between individuals and regional profits, the creation of an internal consumption, the increase of unemployment rate, the public bank reform, the nationalities, the corruption... but, China has demonstrated that knows how to do things in the latter 25 years, so I think that they deserve our confidence. They will know how to continue doing things during the following 25 years, at least. Opposite to this expectation, how we have to place in China from Navarra?